2017
DOI: 10.4315/0362-028x.jfp-16-407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Salmonella Isolates from Chicken Carcasses in Retail Markets in Yangon, Myanmar

Abstract: A cross-sectional investigation was conducted concerning prevalence, antimicrobial resistance, multidrug resistance patterns, and serovar diversity of Salmonella in chicken meat sold at retail in Yangon, Myanmar. The 141 chicken meat samples were collected at 141 retail markets in the Yangon Region, Myanmar, 1 November 2014 to 31 March 2015. Information on hygienic practices (potential risk factors) was retrieved via checklists. Salmonella was isolated and identified according to International Organization for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
2
20
0
3
Order By: Relevance
“…(Sodagari et al, 2015) showed that high antimicrobial resistance rates were observed to nalidixic acid (92.8%), tetracycline (81%), sulfamethoxazole/ trimethoprim (61.2%), streptomycin (56.7%), and kanamycin (36.9%), chloramphenicol (3.6%), amoxicillin-clavulanic acid (5.4%), and ampicillin (11.7%). Moe et al (2017) reported that Salmonella isolates were resistant to trimethoprim-sulfamethoxazole (70.3%), tetracycline (54.3%), streptomycin (49.3%), and ampicillin (47.1%), chloramphenicol (29.7%), amoxicillinclavulanic acid (17.4%), ciprofloxacin (9.4%), tobramycin (8.7%), gentamicin (8%), cefazolin (7.2%), lincomycin-spectinomycin (5.8%), and norfloxacin (0.7%). The obtained results are inconsistent with that reported by Asif et al (2017 ) who showed that S. Enteritidis was resistant to ampicillin (82.2%), tetracycline (80 %), augmentin (77.…”
Section: Resultsmentioning
confidence: 99%
“…(Sodagari et al, 2015) showed that high antimicrobial resistance rates were observed to nalidixic acid (92.8%), tetracycline (81%), sulfamethoxazole/ trimethoprim (61.2%), streptomycin (56.7%), and kanamycin (36.9%), chloramphenicol (3.6%), amoxicillin-clavulanic acid (5.4%), and ampicillin (11.7%). Moe et al (2017) reported that Salmonella isolates were resistant to trimethoprim-sulfamethoxazole (70.3%), tetracycline (54.3%), streptomycin (49.3%), and ampicillin (47.1%), chloramphenicol (29.7%), amoxicillinclavulanic acid (17.4%), ciprofloxacin (9.4%), tobramycin (8.7%), gentamicin (8%), cefazolin (7.2%), lincomycin-spectinomycin (5.8%), and norfloxacin (0.7%). The obtained results are inconsistent with that reported by Asif et al (2017 ) who showed that S. Enteritidis was resistant to ampicillin (82.2%), tetracycline (80 %), augmentin (77.…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug resistant Salmonella spp. and Staphylococcus aureus are a cause of concern since they have been isolated from meat, poultry, and dairy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, NTS prevalence among broiler farms was found to be 45.6% (20) in one study and 64.7% in another (21). A study of poultry meat carcasses in Yangon, Myanmar during 2014-2015 found a 98% prevalence of Salmonella among 141 retail markets (22).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies of poultry and poultry farms from India found 100% of the NTS isolates to be tetracycline resistant (18,19); and one of these the routine use of oxytetracycline as a feed additive. In Myanmar, 54% and 9% of NTS isolates from retail chicken samples were resistant to tetracycline and cipro oxacin, respectively (22).…”
Section: Discussionmentioning
confidence: 99%